Sustainable Digital Marketing Strategies for Enhancing Micro, Small and Medium Enterprises Product Branding - Benardi Benardi; Mohammad Chaidir; Yessica Amelia; Farah Qalbia (Universitas Kristen Indonesia Toraja, 2022)
This research aims to explore sustainable digital marketing strategies that can augment the branding of Micro, Small, and Medium Enterprises (MSMEs). In a rapidly evolving digital landscape, MSMEs face significant challenges in establishing and maintaining their brand presence. The study seeks to address this gap by identifying effective digital marketing approaches that are both sustainable and conducive to the growth of MSMEs. The research adopts a qualitative approach, employing in-depth interviews and content analysis to gather insights from digital marketing experts and MSME owners/managers. The sampling technique involves purposive sampling, targeting individuals with significant expertise in digital marketing and experience working with or within MSMEs. Data analysis follows a thematic approach, wherein interview transcripts and digital content are systematically analyzed to identify recurring themes and patterns related to sustainable digital marketing strategies for MSME branding. Through this process, the research aims to uncover innovative and practical approaches that MSMEs can adopt to enhance their brand visibility, customer engagement, and overall market competitiveness. The findings of this research are expected to contribute to the existing body of knowledge on digital marketing for MSMEs, offering valuable insights for practitioners, policymakers, and researchers alike. By understanding and implementing sustainable digital marketing strategies, MSMEs can not only improve their brand image but also contribute to environmental and societal well-being in the long term.